Characterisation of serine proteinase inhibitors in dry seeds of cultivated pasture grass species : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Plant Biology and Biotechnology at Massey University, Palmerston North, New Zealand - Tasneem, Mohammad (Massey University, 1994)
A chymotrypsin inhibitor has been partially purified from Lolium perenne cv. Grasslands Ruanui that is stable at pH 3 and after heating at 80°C for 10 minutes (acid/heat stable). The inhibitor had a native molecular weight of ca. 20-22 kDa determined using a 2.5 cm x 100 cm Sephadex G-75 column and gel electrophoresis indicated that it may be comprised of two subunits that had molecular weights of ca. 11 kDa and 12 kDa. To determine the occurrence of such inhibitors in other grass species, a survey of seeds from several cultivars of pasture grass species was conducted. Seeds of two cultivars of Festuca arundinaceae, cv. Grasslands Garland and cv. Grasslands Roa have been found to contain the most potent chymotrypsin inhibitory activity of the species surveyed. Seeds of two cultivars of an economically-important genus, Lolium, L. perenne cv Grasslands Ruanui and L. x boucheanum cv Grasslands Greenstone also exhibited significant chymotrypsin inhibitory activity, and so these four species were studied further. Using a 2.5 cm x 100 cm gel filtration column, chymotrypsin inhibitory activity eluted as two peaks in all four cultivars examined which had native molecular weights of ca. 20-22 kDa for peak I and ca. 10-12 kDa for peak II. A ca. 12 kDa chymotrypsin inhibitor was observed in peak 1 of F. arundinaceae cv. Grasslands Garland during gel electrophoresis, and was further purified by ion exchange chromatography. Twelve amino acid residues were sequenced from the N-terminal and the protein was found to be homologous with members of the cereal α-amylase inhibitor family. To purify this activity further, a 10 cm x 100 cm gel filtration column was used. This time trypsin inhibitory activity was also assayed and for all four cultivars, both chymotrypsin and trypsin inhibitory activities co-eluted within two peaks, both with similar molecular weights (peak I, 20-22 kDa and peak II, 10-12 kDa) to that observed previously using the smaller gel filtration column. Gel electrophoresis of peak I from all the four cultivars revealed at least six comparatively lower molecular weight chymotrypsin inhibitors ranging from ca. 12 kDa to 3 kDa for the Festuca cultivars, and at least two ranging from ca. 8 kDa and 12 kDa for the Lolium cultivars. However, higher molecular weight trypsin inhibitors were present in Peak I with 5 inhibitors ranging from ca. 12-18 kDa for Festuca, and three ranging from ca. 12-16 kDa for Lolium. Peak II from all the four cultivars contained only one 12 kDa inhibitor band. The 12 kDa inhibitor is active against both trypsin and chymotrypsin. The 12 kDa inhibitor from peak II of F. arundinaceae cv. Grasslands Garland was purified further using an anhydro-trypsin affinity chromatography and then to homogeneity by reverse-phase HPLC. Two inhibitory peaks were separated that had dual trypsin/chymotrypsin inhibitory activity and had an identical 20 amino acid residues at the N-terminal. The two inhibitor polypeptides were found to be homologous to members of the barley trypsin inhibitor family, but did not share homology with the ca. 12 kDa inhibitor protein purified by ion exchange from gel filtration peak I.
Content removed due to copyright restriction: Tasneem, M., Cornford, C. A., & McManus, M. T. (1994). Characterization of serine proteinase inhibitors in dry seeds of cultivated pasture grass species. Seed Science Research, 4(3), 335-345. Tasneem, M., Cornford, C.A., McManus, M.T., White, D.W.R. (1993). "Purification and characterisation of a proteinase inhibitor from lolium perenne L." Proceedings of the XVII International Grassland Congress : 8-21 February 1993, Palmerston North, New Zealand, Hamilton, New Zealand, Lincoln, New Zealand, Rockhampton, Australia. (1993). Palmerston North, N.Z. : The Association, c1993.
Keywords: Proteinase -- Inhibitors; Plants, Protection of; Grasses -- Diseases and pests